Diagnosis and Management of Secondary HLH/MAS Following HSCT and CAR-T Cell Therapy in Adults; A Review of the Literature and a Survey of Practice Within EBMT Centres on Behalf of the Autoimmune Diseases Working Party (ADWP) and Transplant Complications Working Party (TCWP) - Sandler, Robert David; Tattersall, Rachel Scarlett; Schoemans, Helene; Greco, Raffaella; Badoglio, Manuela; Labopin, Myriam; Alexander, Tobias; Kirgizov, Kirill; Rovira, Montserrat; Saif, Muhammad; Saccardi, Riccardo; Delgado, Julio; et al. (Frontiers in Immunology, 2020)
Introduction: Secondary haemophagocytic lymphohistiocytosis (sHLH) or Macrophage Activation Syndrome (MAS) is a life-threatening hyperinflammatory syndrome that can occur in patients with severe infections, malignancy or autoimmune diseases. It is also a rare complication of haematopoetic stem cell transplantation (HSCT), with a high mortality. It may be associated with graft vs. host disease in the allogeneic HSCT setting. It is also reported following CAR-T cell therapy, but differentiation from cytokine release syndrome (CRS) is challenging. Here, we summarise the literature and present results of a survey of current awareness and practice in EBMT-affiliated centres of sHLH/MAS following HSCT and CAR-T cell therapy. Methods: An online questionnaire was sent to the principal investigators of all EBMT member transplant centres treating adult patients (18 years and over) inviting them to provide information regarding: number of cases of sHLH/MAS seen in their centre over 3 years (2016–2018 inclusive); screening strategies and use of existing diagnostic/classification criteria and treatment protocols. Results: 114/472 centres from 24 different countries responded (24%). We report estimated rates of sHLH/MAS of 1.09% (95% CI = 0.89–1.30) following allogeneic HSCT, 0.15% (95% CI = 0.09–5.89) following autologous HSCT and 3.48% (95% CI = 0.95–6.01) following CAR-T cell therapy. A majority of centres (70%) did not use a standard screening protocol. Serum ferritin was the most commonly used screening marker at 78% of centres, followed by soluble IL-2 receptor (24%), triglycerides (15%), and fibrinogen (11%). There was significant variation in definition of “clinically significant” serum ferritin levels ranging from 500 to 10,000 μg/mL. The most commonly used criteria to support diagnosis were HLH-2004 (43%) and the H score (15%). Eighty percent of responders reported using no standard management protocol, but reported using combinations of corticosteroids, chemotherapeutic agents, cytokine blockade, and monoclonal antibodies. Conclusions: There is a remarkable lack of consistency between EBMT centres in the approach to screening, diagnosis and management. Further research in this field is needed to raise awareness of and inform harmonised, evidence-based approaches to the recognition and treatment of sHLH/MAS following HSCT/CAR-T cell therapy.